2018
DOI: 10.1016/j.celrep.2018.07.045
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Evolution of MERS-CoV to Species Variation in DPP4

Abstract: Middle East Respiratory Syndrome Coronavirus (MERS-CoV) likely originated in bats and passed to humans through dromedary camels; however, the genetic mechanisms underlying cross-species adaptation remain poorly understood. Variation in the host receptor, dipeptidyl peptidase 4 (DPP4), can block the interaction with the MERS-CoV spike protein and form a species barrier to infection. To better understand the species adaptability of MERS-CoV, we identified a suboptimal species-derived variant of DPP4 to study vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
132
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(137 citation statements)
references
References 36 publications
4
132
0
1
Order By: Relevance
“…Notably, although P. pipistrellus bCD26 displayed too weak an interaction with MERS-RBD to be detected by FACS, P. pipistrellus bCD26 still supported MERS-CoV entry ( Fig. 3B), consistent with previous results (17,24). Therefore, all bCD26s tested bound to MERS-RBD and mediated MERS-CoV entry, despite their different binding affinities.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Notably, although P. pipistrellus bCD26 displayed too weak an interaction with MERS-RBD to be detected by FACS, P. pipistrellus bCD26 still supported MERS-CoV entry ( Fig. 3B), consistent with previous results (17,24). Therefore, all bCD26s tested bound to MERS-RBD and mediated MERS-CoV entry, despite their different binding affinities.…”
supporting
confidence: 89%
“…Experimentally, bat CD26s (bCD26s) from a diverse range of bat species can mediate the entry of MERS-CoV (17). Cell lines from certain species of bats also support the replication of MERS-CoV (18).…”
mentioning
confidence: 99%
“…Previous studies showed that CoVs genomes display a high degree of plasticity in terms of gene content and recombination. Furthermore, the relatively large CoV genome increases the probabilities for adaptive mutations, with it being relative easy for the spike protein to exploit multiple cellular receptors for virus attachment and entry [52,[77][78][79]. These features are likely the cause of this alarming propensity of CoVs for host-species expansion.…”
Section: Discussionmentioning
confidence: 99%
“…CoV spike pseudotypes were produced as previously described 31 . 293T cells were seeded onto six-well plates pre-coated with poly-l-lysine (Sigma-Aldrich) and transfected the next day with 1,200 ng of empty plasmid and 400 ng of plasmid encoding coronavirus spike or green fluorescent protein (GFP) as a no-spike control.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, a common problem with studies assessing viral entry in cell types from different species is accurately measuring surface protein expression of the receptor through conventional methods such as flow cytometry. We have previously shown that DPP4 from different species crossreacts differently with the same DPP4 antibody, confounding correlations between receptor expression level and entry 31 .…”
Section: Articlesmentioning
confidence: 99%